Penerapan Nilai-Nilai Hukum Ekonomi Syari’ah pada Produk Murabahah pada BPR Syariah Kota Bandar Lampung - Saleh, Ismail; A. Kumedi Ja’far; Syamsul Hilal; Muhammad Zaki; Maimun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Murabahah is a form of fund raising carried out by sharia banking, both productive (for business activities) and consumptive (for daily needs). Murabahah is the sale and purchase of goods at the original price (capital) with additional agreed profits that are not too burdensome for potential buyers. In a murabahah contract, the seller must disclose the basic price he purchased and determine a level of additional profit. In the murabahah financing product provided by BPR Syari'ah Bandar Lampung, the bank is the capital provider while the customer is the borrower for the purpose of purchasing halal goods, both consumption and investigation, where the bank takes a certain amount of profit (margin) on the cost price of the goods. The payment system is by installments or agreed installments. This type of research is field research. This research was carried out directly in the field using respondent data. The product in murabahah financing at BPR Syariah Bandar Lampung City is that the bank is the capital provider while the customer is the borrower. BPR Syariah Bandar Lampung City applies the maqashid sharia approach in its consumer financing. This can be seen from the consumptive financing provided which has a role and benefit in improving the welfare of members, namely by fulfilling members' dharuriyat and hajjiyat needs and being able to safeguard members' minds and assets.